Soil physicochemical properties in respect to plant health in Ganodermainfested oil palm plantation - Ayundra, Shervinia Dwi; Suwandi, Suwandi; Herlinda, Siti; Hamidson, Harman; Wandri, Ruli; Asmono, Dwi (Journal of Scientific Agriculture, 2022)
Basal stem rot caused by Ganoderma boninense is a major disease of oil palm in Indonesia. Environmental factors associated with disease can be used as the basis for developing disease control. This study aims to describe the physical and chemical properties of oil palm plantations land mineral soil land that is infested with basal stem rot. Soil composite samples were randomly collected from diseased and healthy palm circle from an oil palm plantation in Mesuji, South Sumatra. The results showed that the texture and nutrient status of diseased and healthy plants were not significantly different, namely they had the same low analytical values ​​in terms of the content of N, C-organic, CEC, Mg, Ca, Na, and K2O. The ratios of C/N, exchangeable K and exchangeable acidity in healthy and diseased soils were both moderate to high. The content of available P and total P was very high (43−134 ppm) and was found to be higher in the soil of diseased plants than in healthy plants. These results indicated that high availability of P nutrients may favor G. boninense infection in oil palm plantation.